2020
DOI: 10.1371/journal.pone.0227885
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reproductive effects of S100A9 on bovine sperm and early embryonic development in vitro

Abstract: The phenomenon of aging arises from multiple, complex interactions causing dysfunction in cells and organs. In particular, fertility drastically decreases with age. Previously, we have demonstrated that the functional characteristics of the bovine oviduct and uterus change with the age-dependent upregulation of inflammation and noted that S100A9 triggers inflammatory responses in oviduct epithelial cells. In the present study, we investigated the hypothesis that S100A9 affects reproductive events to aspect suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Actually, although co‐culture with bovine embryos and OECs increased blastocyst formation, co‐culture with embryos and inflamed OECs induced by LPS treatment resulted in a reduction of blastocyst formation. Indeed, we reported that S100A9, one of the candidates of inflammatory trigger produced in bovine OECs, exerted adverse effects on sperm function and embryo development 44 . On the other hand, bovine OECs have an essential role to regulate embryo development and its quality in vitro via oviductal extracellular vesicles 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, although co‐culture with bovine embryos and OECs increased blastocyst formation, co‐culture with embryos and inflamed OECs induced by LPS treatment resulted in a reduction of blastocyst formation. Indeed, we reported that S100A9, one of the candidates of inflammatory trigger produced in bovine OECs, exerted adverse effects on sperm function and embryo development 44 . On the other hand, bovine OECs have an essential role to regulate embryo development and its quality in vitro via oviductal extracellular vesicles 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The S100a9 −/− mouse is viable with normal reproductive ability, 42 and Baker et al observed no S100a9 expressed at 6.5 or 7.5 dpc wild‐type mouse embryos 43 . Nevertheless, Funeshima et al reported that S100a9 induces blastocyst dysfunction by apoptosis 44 . Further studies are needed to investigate the function of S100a9 during embryo hatching and implantation and its influence on term development.…”
Section: Discussionmentioning
confidence: 99%
“…43 Nevertheless, Funeshima et al reported that S100a9 induces blastocyst dysfunction by apoptosis. 44 Further studies are needed to investigate the function of S100a9 during embryo hatching and implantation and its influence on term development. Notably, we observed decreased S100a9 mRNA and protein expression in B-site embryos and the highest expression in C-site embryos, indicating that higher S100a9 expression at hatching stage could be related to an adverse effect on embryonic post-implantation development, poor implantation, and low birth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, S100A9 levels are elevated in the endometrial tissue of women with a recurrent history of early pregnancy loss [30,31]. Recently, we reported that exposure to S100A9 adversely affected sperm function and embryo development, and stimulated the production of inflammatory cytokines in the oviduct [32]. From all these data, we hypothesized that S100A9 may be one of the key factor linking NLRP3 inflammasome activation and HDP disorder.…”
Section: Introductionmentioning
confidence: 96%